2009
DOI: 10.5194/nhess-9-501-2009
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity anomalies prior to the 13 December 2008, <i>M<sub>s</sub></i>=5.7 earthquake in Central Greece

Abstract: Abstract.This investigation has applied a recent methodology to identify seismic quiescence and seismic acceleration, prior to the occurrence of the 13 December 2008, M s =5.7 earthquake in Central Greece. Anomalous seismic quiescence is observed around the epicentral area almost twelve years prior to the main shock and it lasted for a period of about four and a half years. After this period an acceleration in seismic activity began and lasted until the main shock. Modeling this seismic sequence with the time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…These methods are ROC, PPV, and Shannon information. We note that quiescence has been identified as a precursor to major earthquakes in previous research (Chouliaras, 2009; Habermann, 1988; Huang et al., 2001; Kanamori, 1981; Katsumata, 2011; Main & Meredith, 1991; Nanjo, 2020; Rundle et al., 2003, 2011; Tormann et al., 2010; Wiemer & Wyss, 1994; Wyss & Habermann, 1988).…”
Section: Discussionsupporting
confidence: 51%
“…These methods are ROC, PPV, and Shannon information. We note that quiescence has been identified as a precursor to major earthquakes in previous research (Chouliaras, 2009; Habermann, 1988; Huang et al., 2001; Kanamori, 1981; Katsumata, 2011; Main & Meredith, 1991; Nanjo, 2020; Rundle et al., 2003, 2011; Tormann et al., 2010; Wiemer & Wyss, 1994; Wyss & Habermann, 1988).…”
Section: Discussionsupporting
confidence: 51%
“…We note that many other authors have discussed the importance of seismic quiescence, which clearly can only be identified in comparison to activation. These include Kanamori (1981); Wiemer and Wyss (1994); Wyss and Habermann (1988); Chouliaras (2009); Katsumata (2011); Ben-Zion and Zaliapin (2020); Varotsos et al (2011Varotsos et al ( , 2014Varotsos et al ( , 2020; Zaliapin and Ben-Zion (2022).…”
Section: Discussionmentioning
confidence: 99%